1985
DOI: 10.1288/00005537-198507000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effects of ionizing radiation on the ear

Abstract: The question of damage to the ear from exposure to ionizing radiation was addressed by exposing groups of chinchillas to fractioned doses of radiation (2 Gy per day) for total doses ranging from 40 to 90 Gy. In order to allow any delayed effects of radiation to become manifest, the animals were sacrificed two years after completion of treatment and their temporal bones were prepared for microscopic examination. The most pronounced effect of treatment was degeneration of sensory and supporting cells and loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
1
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 18 publications
1
63
1
1
Order By: Relevance
“…All these were acute and transient complaints which may start as early as immediately after the radiotherapy, may appear later, might last till 6 months. Bohne et al [1] in their study have mentioned slight pain or discomfort in the ear as well as tinnitus as symptoms of serous otitis media resulting due to ionizing radiation of the ear. They attributed tinnitus to acute changes consisting of edema of the middle ear mucosa, radiation otitis media and transient vasculitis of the vessels of the inner and middle ear.…”
Section: Observation and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All these were acute and transient complaints which may start as early as immediately after the radiotherapy, may appear later, might last till 6 months. Bohne et al [1] in their study have mentioned slight pain or discomfort in the ear as well as tinnitus as symptoms of serous otitis media resulting due to ionizing radiation of the ear. They attributed tinnitus to acute changes consisting of edema of the middle ear mucosa, radiation otitis media and transient vasculitis of the vessels of the inner and middle ear.…”
Section: Observation and Discussionmentioning
confidence: 97%
“…There are many studies which mention hearing loss as a consequence of irradiation of the hearing apparatus. Bohne et al [1] found that conductive impairments occur during therapy but these usually disappear after completion of treatment and resolution of the radiation otitis media. L F Wang et al [6] concluded that hearing deterioration may begin as early as 3 months post RT.…”
Section: Observation and Discussionmentioning
confidence: 99%
“…(3) Higher frequencies were more commonly affected than lower frequencies [2,13,20]. There is a radiation induced pathophysiologic changes of the auditory system starting from the Eustachian tube to the brain stem [1,3,13,17] and the mechanism of SNHL is not clear. However, there is clear correlation between missing hair cells on the organ of Corti and radiation dose [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is clear correlation between missing hair cells on the organ of Corti and radiation dose [2]. In addition, outer hair cells of higher frequency area are more commonly affected [1,17] and it is closely correlated with clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have received radiotherapy for NPC, the incidence of eventual SNHL is reportedly as high as 50% (Low and Fong, 1998). Several studies have proved that the death of cochlea hair cell is responsible for the radiation-induced SNHL (Bohne et al, 1985;Honore et al, 2002;Linskey and Johnstone, 2003;…”
Section: Introductionmentioning
confidence: 99%